18F-Fluoroethylcholine (18F-Cho) PET/MRI Functional Parameters in Pediatric Astrocytic Brain Tumors. (January 2015) - Fraioli, Francesco; Shankar, Ananth; Hargrave, Darren; Hyare, Harpreet; Gaze, Mark N.; Groves, Ashley M.; Alongi, Pierpaolo; Stoneham, Sara; Michopoulou, Sofia; Syed, Rizwan; Bomanji, Jamshed B.
<x xml:space="preserve">Abstract</x> Purpose To examine the feasibility of simultaneous acquisition of 18F-fluoroethylcholine (18F-choline) PET and functional MRI (standardized uptake value [SUV]max/mean and apparent diffusion coefficient [ADC]mean), using a hybrid PET/MRI scanner, for diagnosis and response assessment in a cohort of children with astrocytic brain tumors. Methods 18F-choline PET/MRI scans were performed in 12 patients with proven astrocytic tumors. Eight patients simultaneously underwent 18F-choline PET/MR follow-up scans after treatment. Uptake in the lesion above the normal brain activity was considered indicative of a positive scan. Maximum and mean SUVs (SUVmax and SUVmean) and mean ADC (ADCmean) of the whole tumor region of interest were assessed. Lesion size and contrast enhancement were recorded. For all tumors, the association between ADCmean and SUVmean/SUVmax values were assessed using the Spearman correlation coefficient. Results At baseline, the areas of 18F-choline uptake matched areas of contrast enhancement and restricted diffusion. There was a negative correlation trend between SUVmax and ADCmean and a positive correlation trend between SUVmax and tumor size. There was concordance between reduction in tumor size and reductions in SUVmax and SUVmean in 4 children, in three of whom ADCmean values were increased. In 2 patients, tumor size remained stable whereas SUVmax and SUVmean values were increased with reduction in the ADCmean values. Additionally, in 2 children, cross-sectional MRI showed an increase both in tumor size and SUVmax but a reduction in ADC values. Conclusions Simultaneous 18F-choline PET/MRI is a promising and reliable imaging tool for children with astrocytic tumors, as it permits monitoring of morphological and metabolic response and changes during therapy.